Remittance inflow and economic development: interaction with financial inclusion and human capital - Saydaliyev, Hayot Berk; Lee, Chin; Mohamed, Azali (Taylor and Francis Group, 2020)
This paper used the dynamic panel data technique to examine the combined indirect effect of remittance inflows via human capital and financial inclusion on economic growth in developing and developed countries over the period between 2007 and2 018. The results from the endogeneity-robust System Generalized Method of Moments (GMM) analysis revealed that with with financial inclusion and human capital, are engines of economic growth in remittance-receiving developing countries. Specifically, better financial inclusion absorbs and efficiently channel remittance inflows into proper and productive economic activities, while developed human capital directly encourages robust economic activities. Therefore, this paper provides insights into the mechanisms that boost remittances’ effect on economic growth, i.e. financial inclusion and human capital. Accordingly, we recommend that regulatory frameworks aiming to encourage inward remittances should consider developing financial inclusion and human capital to leverage remittance funds for developmental agendas.